An analysis of transition-resulted goal scoring patterns in football leagues: a comparison of the first 5 rounds and the last 5 rounds prior midway of the season - Eusebio, P.; Prieto-González, P.; Marcelino, R. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Objective This study investigated the concept of `game style` in football, focusing on a team`s distinctive approach characterized by tactics, formations, and strategies. The objective is to compare goal-scoring patterns related to "non-offensive transition," "set pieces," "offensive transition," and "positive outcomes" across different league groups.